Western Armenian Fairy Tale Writing at the End of the XIX Century and the Beginning of the XX Century (Tlkatintsi, Msho Gegham, Zardaryan) - Hayriyan, Lusine (Bulletin of Yerevan University B: Philology, 2022)
In this paper, I will present famous Armenian authors from the end of the XIX century and the beginning of the XX century who collected folklore and used it as literary material. Tlkatinci, Msho Gegham, and Rouben Zardaryan saw fairy tales at the crossroads of different genres and created inter-genre works. I will discuss how these authors used elements from fairy tales in other genres and how folklore materials have been developed. It is also worth noting that all the studied authors were followers of the same literary movement.